La migration forcée des jésuites de l’Empire espagnol en Italie (1767-1801): intégration créative et identité religieuse - Nicolas de Ribas (Les Cahiers ALHIM)
The work of enlightened Jesuits from Latin America and living in Italy reveals a large and diversified cultural panorama that goes beyond great signatures such as Viscardo’s or Clavigero’s. From the eighteenth century Italian peninsula a melancholy, but also committed literature eventually became the banner of American patriotism. Condemning Spanish colonialism these priests’ prosaic or poetic works give a subjective image of the Jesuits’ exile from a human and telltale point of view. With their vast culture and great sensibility Jesuit writers showed the tragedy of what was euphemistically called the extrañamiento, the forced migration that divided the Jesuit order on account of their Spanish or American origins. Even though quite a few historians tend to see the Jesuits’ eviction as far less inhuman and more “enlightened” than that of the Jews or the Moors, the trauma of an exile expressed in the elegiac poems of Velasco or in those of Landívar is not to be neglected. At a distance from the actual events an extensive bibliography that praised Creole and Native American cultures reveals sentiments dictated by grief and separatist thoughts conditioned by passion and nostalgia. It is thus necessary to stress the protean character of these writings while considering them within a religious identity deeply marked by intellectual activism.